Superdense beaming of axion dark matter in the vicinity of the light cylinder of pulsars. Issue 8 (1st August 2022) - De Miguel, Javier; Otani, Chiko
Abstract: In this article we treat the non-adiabatic photon-to-axion resonant conversion of curvature radiation, synchrotron emission and inverse Compton scattering dominating the spectral density function of pulsars. First, we introduce emission models and benchmark observational data. We adopt a state-of-the-art density profile that relieves tension with the quantum electrodynamics vacuum polarization effect in highly magnetic stars, leading to efficient mixing. Then, we estimate the dark matter flux induced by photon-axion oscillation across the light cylinder of the neutron star. We find that pulsars might produce axion overdensities many orders of magnitude over the occupation number of dark matter in the Galactic halo within a broad parameter space. We point out possible new methods for axion detection derived from these results and other future lines of work.